Odpowiedź :
Odpowiedź:
a) 4 : 1/2- 14/3*9/7 ( skracamy 3 i 9 przez 3, oraz 14 i 7 przez 7)=
=4 *2/1 - 2*3= 8- 6= 2
b) 6 i 1/3 *( 2/3 + 3/4)= 19/3 *( 8/12 + 9/12)= 19/3 *17/12= 323/ 36=8 i35/36
c) ( 2/3 + 5/6 ) :3 - ( 7/9 - 1/2)= ( 4/6 + 5/6 ) :3 - ( 14/18- 9/18)=
=9/6 *1/3 - 5/18)( skracamy 9 i 3 przez 3)= 3/6- 5/18= 9/18- 5/18= 4/18= 2/9
d) 2 i 7/12 - 2/3 : 8 + 7/8= 2 i 7/12 - 2/3*1/8+ 7/8( skracamy 2 i 8 przez 2)=
= 2 i 7/12 - 1/12 + 7/8= 2 i 6/12 + 7/8= 2 i 1/2 +7/8= 2 i 4/8+7/8=
= 2 i 11/8= 2 i 3/8
e) 1 i 4/5 - 2/5 : 5/4= 1 i 4/5 - 2/5 *4/5= 1 i 4/5- 8/25=
=1 i 20/25- 8/25= 1 i 12/25
f) 3 i 3/4 : 2/3 : 8 + 1/8 *16/5 = 3 i 3/4 : 2/3 *1/8 + 1/8 *16/5 ( skracamy 16 i 8 przez
8)= 15/4 *3/2*1/8 + 2/5= 45/64 +2/5 = 225/320 + 128/320=
= 353/320= 1 i 33/320
Szczegółowe wyjaśnienie: